Peran Media Kehumasan dalam Meningkatkan Mutu Pendidikan - Basit, Abd (Institut Agama Islam Negeri Lhokseumawe, 2019)
The development of education is progressing. It is characterized by the quality and quantity of educational institutions are getting better. Success and success cannot be separated from the role of all education components that are able to perform their functions and duties respectively well. A good system will result in a good process and the results achieved will be good too. Here is the vital position of the public relations role in socializing an educational institution to the public. Efforts made by schools in introducing educational institutions through public relations activities, so the public relations department plays an important role in developing the institution into an educational alternative for the community to educate their foster children to be a bright young generation, character and character, also beneficial to society.